Aerodynamic Comparison on Different Types of Two-Seater Car Using Ansys CFX - Zulkarnain, Nurul Izzati; Abdullah, Mohammad Kamil (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Two-seater cars are often linked to aerodynamics because of their small size and sporty aesthetics. As these cars are focused on speed, performance, and handling, their design can have a significant impact on their aerodynamic performance. The aim of this study is to evaluate aerodynamic performance on different two-seater cars using ANSYS CFX. The design of the model is derived from the configuration of two-seater cars, featuring a total of four distinct body shapes which are Nissan Skyline, Porsche 918 Spyder, Bugatti Chiron and Ford Mustang. The simulation utilizes element size 0.03mm for all car models, given its lowest percentage difference observed among the tested element sizes. In conclusion, Nissan Skyline, Porsche 918 Spyder and Bugatti Chiron have better aerodynamic efficiency.